Semiochemical interaction between Myopopone castanea Smith with its prey Oryctes rhinoceros linn. Larvae - Widihastuty,; Rini Susanti,; Wizni Fadhillah, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Ant species, Myopopone castanea is a predator for immature of Oryctes rhinoceros. The ants used semiochemical compounds in communications between individuals both in the same species or different species. This study aims to determine the semiochemical compounds that play a role in the relationship between the interaction of M. castanea as predators and their prey larvae O. rhinoceros. The results showed that the volatile compounds from GC-MS analysis of M. castanea ants wood nest were hydrocarbons compounds. In contrast, volatile compounds from GC-MS study of O. rhinoceros larvae were 5H-1 pyrindine compounds, carboxyclic acid an hydrocarbon compounds. The results of the odour detection test on M. castanea ants in the Y tube showed that the choice of M. castanea in the combined aroma of palm oil sawdust and O. rhinoceros larvae was higher (78%) than the choice only for palm oil stem sawdust (54%) and only O. rhinoceros larvae (48%). The combination of palm oil sawdust and O. rhinoceros larvae makes the volatile compounds stronger so that the ants prefer this scent. The semiochemical compounds in rotting oil palm stems can be a medium of interaction between M. castanea as and O. rhinoceros larvae.